2019
DOI: 10.1021/acssensors.9b01604
|View full text |Cite
|
Sign up to set email alerts
|

Microcantilever Array Biosensor for Simultaneous Detection of Carcinoembryonic Antigens and α-Fetoprotein Based on Real-Time Monitoring of the Profile of Cantilever

Abstract: A microcantilever array biosensor based on a sandwich structure has been developed for simultaneously measuring two biomarkers carcinoembryonic antigen (CEA) and α-fetoprotein (AFP) via an optical readout techniquereal-time monitoring of the profile of cantilever. First, the aptamers of CEA and AFP were self-assembled on their respective cantilevers. After the adsorption of the mixture of CEA and AFP, further specific interaction was performed via the addition of the antibodies specific to each target. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Specifically, the positive V th value in the anti-AFP-modified OFET-based protein biochip for 1 μg/mL single-AFP-biomarker was 3.033 ± 0.093 V and in the anti-CEA-modified OFET-based protein biochip for 1 μg/mL single-CEA-biomarker was 7.503 ± 0.245 V. In contrast, a control experiment using nonspecific human serum albumin (HSA) showed a negligible V th response, reflecting the lack of binding events in the sensing area. In addition, with different concentrations of the single-AFP-biomarker and the single-CEA-biomarker ranging from 100 pg/mL to 1 μg/mL, the limits of detection were, respectively, determined to be 0.176 pM for the AFP biomarker and 65 fM for the CEA biomarker, which were lower than the cut-off values (10 ng/mL for the AFP biomarker and 5 ng/mL for the CEA biomarker). , The achieved detection ranges for both biomarkers are comparable to commercial techniques. …”
Section: Resultsmentioning
confidence: 76%
“…Specifically, the positive V th value in the anti-AFP-modified OFET-based protein biochip for 1 μg/mL single-AFP-biomarker was 3.033 ± 0.093 V and in the anti-CEA-modified OFET-based protein biochip for 1 μg/mL single-CEA-biomarker was 7.503 ± 0.245 V. In contrast, a control experiment using nonspecific human serum albumin (HSA) showed a negligible V th response, reflecting the lack of binding events in the sensing area. In addition, with different concentrations of the single-AFP-biomarker and the single-CEA-biomarker ranging from 100 pg/mL to 1 μg/mL, the limits of detection were, respectively, determined to be 0.176 pM for the AFP biomarker and 65 fM for the CEA biomarker, which were lower than the cut-off values (10 ng/mL for the AFP biomarker and 5 ng/mL for the CEA biomarker). , The achieved detection ranges for both biomarkers are comparable to commercial techniques. …”
Section: Resultsmentioning
confidence: 76%
“…Therefore, Nbs clearly outperformed conventional antibodies thanks to their small-size format and facile decoration with a C-terminus thiol group. Thus far, microcantilever immunosensors in static mode achieved a limit of detection (LOD) of 1-5 ng•mL −1 for tumor marker detection using intact Abs as receptor molecules [24,25], some of which only slightly improved the sensitivity, even when using a sandwich assay [23]. However, the LOD observed here, without complicated labellings and additional manipulations, was far superior to these reported values and was based on the unique mechanical properties of Nbs.…”
Section: Nanomechanical Detection Of Tumor Markersmentioning
confidence: 62%
“…Studies have shown that microcantilever sensors are sensitive, label-free, rapid, and real-time [21,22]. Such attractive advantages make microcantilever biosensors widely exploited in proteomics, drug screening, and environmental monitoring [23][24][25]. However, for disease diagnosis, especially early cancer diagnosis, there is a long way to go in term of developing microcantilever sensing method to resolve the sensitivity bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by the outstanding sensitivity and selectivity of the nanochannel immunosensor, we further evaluated the potential application of the AFP assay in clinical diagnosis from a human blood serum. Considering the low concentration of AFP (less than 25 ng mL –1 ) in healthy human serum, the applicability was assessed in healthy human serum samples using the standard addition method. The I–V properties of the MoS 2 -Ab 2 /AFP/Ab 1 /Pt/TiNM for these spiking samples are shown in Figure A, and the corresponding Δ I values at −1.0 V are shown in 5B.…”
Section: Resultsmentioning
confidence: 99%